Peer Education Improves Coping and Self Efficacy in Facing Bullying in Adolescents: Edukasi oleh Teman Sebaya Meningkatkan Koping dan Self Efficacy Menghadapi Bullying pada Remaja - Ignasia Yunita Sari; Indah Prawesti; Pipit Fibrianti Permatasari (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the influence of peer education on adolescent coping strategies and self-efficacy in addressing bullying behaviors within a junior high school context. Focusing on a group of 31 randomly selected students aged 13-15 years, the research employed a pre-experimental design with pre-test and post-test assessments using the Brief Coping Orientation to Problems Experienced (Brief COPE) and the modified General Self-Efficacy Scale (GSES). Results revealed a significant improvement in coping skills, with an increase from 23 to 28 students demonstrating effective coping after peer education. Similarly, students classified as having high self-efficacy rose from 20 to 24 following the educational intervention. The findings underscore the positive impact of peer education on adolescent coping and self-efficacy in combating bullying behavior. This study calls for further exploration of factors influencing coping strategies in addressing bullying among adolescents, aiming to enhance intervention approaches and create a supportive school environment. Highlights: Significant Improvement: Peer education demonstrates a substantial positive influence on adolescent coping strategies and self-efficacy in dealing with bullying behavior. Effective Intervention: The study highlights the effectiveness of peer-led education in fostering improved coping mechanisms and self-efficacy among adolescents facing bullying challenges. Enhancing School Environment: Findings emphasize the need to explore and develop factors that influence coping strategies, contributing to the creation of a more supportive and resilient school environment for adolescents. Keywords: Peer education, Bullying behavior, Adolescent coping, Self-efficacy, Junior high school.